Detection of genetic variation and base modifications at base-pair resolution on both DNA and RNA - Zhen Wang (Nature Portfolio, 2021)
Wang et al. show how genetic sequence and base modifications can be detected simultaneously on single molecules of both DNA and RNA using magnetic tweezers. They also demonstrate an amplification-free CRISPR/Cas9-based strategy for isolating target regions from native DNA and apply this approach to the isolation of targets from E. coli and human genomic DNA.